A new species of the genus Tatargina (Lepidoptera, Erebidae, Arctiinae) from Cambodia - Bayarsaikhan, Ulziijargal; Ko, Jae˗ho; Kwon, Hyung-Wook; Bae, Yang-Seop (Zootaxa, 2020)
A new species of the Tatargina Butler, T. erythromelaena Bayarsaikhan & Bae, n. sp., is described from Cambodia, with a recorded species, T. picta (Walker). Illustrations of adults and male genitalia of Cambodia and Thailand species are presented.